Prologue to the Symposium Management of an ovarian mass - Celis López, Alfredo (2019)
Ovarian tumors occur mostly during the reproductive stage. Of women and therefore constitutes one of the problems most common that the gynecologist has to deal with in their daily practice. Approximately 10% of these tumors will need surgical treatment To be resolved.